Proposed new interior design of Zen Japanese Restaurant for Super Dining Sdn. Bhd. at 12-A, Persiaran Greentown 8, Pusat Perniagaan Greentown 30450 Ipoh Perak / Mohd Fadzaly Mohd Padin - Mohd Padin, Mohd Fadzaly (Faculty of Architecture, Planning and Surveying, 2010)
This final project is to propose new interior design of Zen Japanese Restaurant for Super Dining Sdn.Bhd. At 12-A, Persiaran Greentown 8, Pusat Perniagaan Greentown 30450 Ipoh Perak. In Malaysia, japanese restaurant is not really well known. It’s diffrent between sushi restaurant and ala carte japanese restaurant that making a japanese food in japanese method. To collect the data collection, interview with the client have been done and some discussion has been carried out. From client I will get the requirement of what client needs. Besides that, research has been done by internet, magazines, and newspaper to support my data and increase the understanding of the project. All the data collection will be the guideline on design process and references to develop the idea of design.